2021
DOI: 10.1371/journal.pone.0252150
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of SNIP test and optimal number of maneuvers in 6-11 years healthy children

Abstract: Background and purpose Sniff nasal inspiratory pressure (SNIP) is a voluntary inspiratory maneuver measured through a plug occluding one nostril. The investigation of the number of maneuvers necessary to reach the highest peak of SNIP in pediatric populations has been inconsistent. Thus, this study aimed to assess the reliability of SNIP in healthy children aged 6 to 11 years according to sex and age group, and to determine the optimal number of SNIP maneuvers for this age group. Methods This cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(50 reference statements)
3
3
0
Order By: Relevance
“…They also showed good reliability and reported that 42% of the highest SNIP values were among the 6th and 10th maneuvers; 3% of participants achieved the same performance over 12 maneuvers. Corroborating Lofaso et al [ 7 ] and Marcelino et al [ 28 ], we found that 75% (24 maneuvers) of the highest SNIP values and 69% (22 maneuvers) of the reproducible maneuvers were obtained in the last ten maneuvers. Also, 65% of the highest SNEP values and 62% of the reproducible maneuvers were achieved among the 11th and 20th maneuvers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…They also showed good reliability and reported that 42% of the highest SNIP values were among the 6th and 10th maneuvers; 3% of participants achieved the same performance over 12 maneuvers. Corroborating Lofaso et al [ 7 ] and Marcelino et al [ 28 ], we found that 75% (24 maneuvers) of the highest SNIP values and 69% (22 maneuvers) of the reproducible maneuvers were obtained in the last ten maneuvers. Also, 65% of the highest SNEP values and 62% of the reproducible maneuvers were achieved among the 11th and 20th maneuvers.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, SNIP is a widely used test [3,10,23], that is recommended to assess individuals with respiratory diseases (e.g., chronic obstructive pulmonary disease and neuromuscular diseases) [24,26]. Other studies confirmed the good reliability of SNIP for assessing healthy adults [25][26][27] and children aged 8 to 11 years [28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Taking this into account and the fact the investigator needed to record the measurement, it would have been difficult to complete this process within an interval less than 30 s. As the present study included only healthy subjects, we cannot conclude whether 30 s is an appropriate rest interval for patients who may be prone to fatigue, such as those with NMDs. However, our findings are supported by the fact that 30 s intervals have previously been used in NMD and lung disease patients, with no adverse events or significant impact on SNIP values reported [ 11 , 19 ] and in healthy children [ 25 ].…”
Section: Discussionsupporting
confidence: 80%
“…The test was carried out in a sitting position, with the use of three to five repetitions for each nostril. The plug was sterilized after use [24,25].…”
Section: Outcome Measuresmentioning
confidence: 99%